Wien und die jüdische Erfahrung 1900-1938 : Akkulturation - Antisemitismus - Zionismus - Stern, Frank 1944- (Böhlau, 2009)
The growing integration and participation of the Jewish population in politics, society, culture arts and religion shaped these spheres in Vienna during the time of the First Republic. Social dynamics of the young democracy, interplay of the different Jewish milieus, immigration from Eastern and Southeastern Europe as well as the growing cultural links with Berlin, Budapest, Paris and Prague made Austrian-Jewish culture in all areas of the development of the city of Vienna highly influential. Antidemocratic tendencies, especially antisemitism, influenced both the discourses on current events and inner-Jewish debates such as the role of Jewish religion, acculturation and Zionism. The publication "Wien und die jüdische Erfahrung 1900 - 1938. Akkulturation - Antisemitismus, Zionismus" initiated by Univ.-Prof. Frank Stern and Mag. Barbara Eichinger from the Institute for Contemporary History, University of Vienna, shows the state of the art of research on this subject.